PUBLIC DEBATE ABOUT THE CONDITION OF THE MAPUCHE - Millacura Salas, Claudio (Revista de Historia Social y de las Mentalidades, 2024)
During the first months of the Ricardo  Lagos Escobar government (2000-2006),  this prompted several measures in favor of  Indigenous People. Soon those measures  were rejected by the most conservative  part of chilean society. One of its major  representative in the area of history, by  means of letters published released by the  favorite newspaper of the sector, not only  took charger of delegitimize the actions taken  by the government but also the demands of  indigenous people. This dispute beyond align  the chilean society following the tenets of each  one of the positions, exposed the ideology that  fuels the economic system in Chile and their  advocates.   Mapuche
Keywords: Mapuche; History; Discourse analysis; Controversy; Economic model